CAUSES, DIAGNOSTICS AND PSYCHOLOGICAL IMPACT OF PREMATURE OVARIAN INSUFFICIENCY- REVIEW OF LITERATURE - Natalia Karpowicz; Natalia Pacocha; Julia Kaszucka; Justyna Popczyńska; Agnieszka Raczyńska; Małgorzata Krzyżanowska; Marta Zgierska; Jakub Jędrychowski; Kinga Kosiec; Oliwia Krzemień (International Journal of Innovative Technologies in Social Science, 2024)
Premature ovarian insufficiency (POI) before the age of 35 occurs in 1 in 250 women. It can develop on a genetic basis, but also may be a consequence of iatrogenic interventions, such as surgery, radiation or chemotherapy. The patients with impaired ovarian endocrine function may experience disruptive menopausal symptoms. Estrogens deficiency consequences include increased risk of osteoporotic fractures and cardiovascular events. Lack of folliculogenesis and ovulation results in infertility. Detailed review of the literature was conducted to summarize current knowledge about causes, diagnostics, psychological impact and novel therapeutic methods in POI. Review of the literature was conducted by searching the PubMed database and Google Scholar. Checking the literature was carried out by the following keywords: ‘premature ovarian insufficiency’, ‘POI’, ‘etiology’, ‘symptomatology’, ‘treatment’, ‘pathogenesis’, ‘genes’, ‘mutations’, ‘psychological effects’, ‘oncofertility’. The multifactorial aetiology of POI, including genetic, autoimmune, iatrogenic, and environmental factors, highlights the complexity of this condition and the need for a multidisciplinary approach to diagnosis and treatment. Progress in molecular methods of genetic diagnostics, such as whole-genome sequencing, may help identify causative mutations in a larger proportion of idiopathic cases. Hormonal replacement therapy is the gold standard for alleviating menopausal symptoms, maintaining bone density, and reducing cardiovascular risk. The psychological impact of POI cannot be underestimated, with many patients experiencing significant emotional distress and dissatisfaction with the manner in which their diagnosis is delivered. Healthcare providers must prioritize sensitive and informative communication, while also referring patients to appropriate sources of emotional support.